DEVELOPMENT STRATEGY OF ECOTOURISM MARINE SUSTAINABLE IN INDONESIA - Ni Ketut Arismayanti (Centre For Tourism Planning and Development, 2017)
Indonesia is a maritime country and the largest island in the world. Indonesia has a wealth of marine and coastal very abundant. But in reality, especially in the field of tourism has not been fully utilized for tourism activities. Marine tourism is a new type of tourism development that began to develop and favored travelers. In the development of this type of tourism should be recognizable the characteristics of marine tourism in order to advance in the development and management can preserve the marine ecosystems in a sustainable environment. Tourism development is expected to occurring conservation in marine and coastal areas towards of sustainable development. This study aims to identify the potential for marine ecotourism located in Indonesia; analyze the internal and external environment marine ecotourism; analyzing strategies and develop a sustainable marine ecotourism development program in Indonesia. This study uses qualitative descriptive analysis techniques and SWOT analysis. The reference review in this research is the concepts of a strategy for tourism development, ecotourism, marine tourism, sustainable tourism. The strategy can be applied related to the development of sustainable marine ecotourism in Indonesia, namely: strategy of regional development and marine ecotourism product through empowerment of local communities; strategy of developing a network of marine industry and tourism; Infrastructure development strategy (infrastructure and means of supporting the principal and marine tourism); strategy of marketing development marine ecotourism product; strategy of coastal areas planning; strategy for increasing the security of maritime tourism; and strategies for institutional development and human resources and marine tourism. Sustainable marine ecotourism development should be prepared and planned and managed well, so it can directly and positively contribute to the public welfare, poverty reduction, rural development, preservation of culture and society, and environmental protection.